1996
DOI: 10.1074/jbc.271.34.20763
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of c-Met in Liver Metastatic B16 Melanoma Cells Depends on Both Substrate Adhesion and Cell Density and Is Regulated by a Cytosolic Tyrosine Phosphatase Activity

Abstract: Serial selection in vivo for liver colonization of B16 murine melanoma cells consistently resulted in cell lines expressing elevated amounts of the hepatocyte growth factor/scatter factor receptor (c-Met), which is constitutively activated in the absence of its cognate ligand. In this paper we present evidence suggesting that c-Met constitutive activation in liver-specific B16 melanoma cells depends on both receptor concentration on the cell surface and a cytosolic tyrosine phosphatase activity. In fact, c-Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
5
29
1
Order By: Relevance
“…Constitutive activation of Met, as observed in the present study, has previously been reported from a gastric carcinoma cell line (GTL-16) , and also in murine melanoma cells (B16-LS9) (Rusciano et al, 1996). GTL-16 cells overexpress Met as a result of MET gene amplification .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Constitutive activation of Met, as observed in the present study, has previously been reported from a gastric carcinoma cell line (GTL-16) , and also in murine melanoma cells (B16-LS9) (Rusciano et al, 1996). GTL-16 cells overexpress Met as a result of MET gene amplification .…”
Section: Discussionsupporting
confidence: 88%
“…Thus, it is possible that an overexpression leads to constitutive activation of the receptor proteins. Rusciano et al (1996) suggested that the ligand-independent activation observed in the B16-LS9 cells may be caused by the high number of receptors present on the cell surface, leading to spontaneous dimerization and phosphorylation. However, Ferracini et al (1995) reported very high expression of Met in the osteosarcoma cell line, U-2 OS, without any constitutive phosphorylation of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed that abundantly expressed Met in SNU-5 and SNU-638 was constitutively autophosphorylated without exogenous HGF treatment or autocrine HGF stimulation. Rusciano et al suggested that the ligandindependent activation observed in the B16-LS9 cells was caused by the high number of receptors present on the cell surface, leading to spontaneous dimerization and phosphorylation (Rusciano et al, 1996). Consistent with these findings, the ligand-independent activation of Met was observed only in cell lines where Met was overexpressed (Ponzetto et al, 1991).…”
Section: Discussionmentioning
confidence: 86%
“…As expected, constitutive activation of Met was observed in SNU-484 cells (Figure 3, middle panel). Interestingly, the Met expressed in SNU-5 and SNU-638 was also highly phosphorylated, even though the HGF produced by these cells was negligible according to ELISA assay (data not shown) possibly due to the ligand-independent activation of Met via spontaneous dimerization and phosphorylation when overexpressed (Rusciano et al, 1996). To further demonstrate autocrine HGF-Met signaling in SNU-484 cells, Met in SNU-484 cells was immunoprecipitated and the degree of tyrosine phosphorylation was assessed.…”
Section: A Utocrine H G F-m Et Signaling In Sn U -484 Cell Linementioning
confidence: 97%
“…In contrast to this finding, other reports have revealed that c-met is predominantly expressed in the basolateral membrane domains of human gut cells and a variety of other polarized epithelial cells [10,11,24]. Immunofluorescent staining of mouse intestinal tissue was performed using D1 monoclonal antibodies that selectively bind c-met [19].…”
Section: C-met and Gtk Are Colocalized At Some Sites In The Brush Bormentioning
confidence: 91%